Experiment study on CO2 adsorption performance of thermal treated coal: Inspiration for CO2 storage after underground coal thermal treatment. (1st September 2022) - Shi, Qingmin; Cui, Shidong; Wang, Shuangming; Mi, Yichen; Sun, Qiang; Wang, Shengquan; Shi, Chenyu; Yu, Jizhou
Abstract: Underground coal thermal treatment is a clean method of coal utilisation. Pyrolytic semi-coke provides a good storage vehicle for CO2 geological storage, but there are few studies on the CO2 adsorption capacity of pyrolytic semi-coke. To investigate the CO2 storage potential of thermal treated coals, scanning electron microscopy, low temperature nitrogen adsorption, low-field nuclear magnetic resonance and thermogravimetric analysis were used in this paper to analyze the differences and the influence mechanisms of different thermal treated coals for CO2 adsorption. The results showed the CO2 maximum adsorption amount of different thermal treated coals decreased and then increased as the thermal treatment temperature increased, reaching a minimum at 773.15 K. Although the maximum adsorption amount of 773.15 K thermal treated raw coal was disadvantageous, the gas pressure <4.49 MPa showed superior adsorption advantage over the 303.15 K thermal treated coal. However, the KCl-impregnated coal showed an overall low adsorption capacity attributed to crystal blocking effects and catalysis. Although the adsorption pores of the high temperature thermal treated coals were substantially reduced, their ability to adsorb CO2 was significantly higher than that of the low temperature thermal treated coals. Furthermore, the number of adsorption pores was closely related to CO2 adsorption. Highlights: The pyrolytic semi-coke based on UCTT is a good vehicle for CO2 storage. The swelling effect of the coal at 573.15 K reduced the adsorption properties. High temperature treated coal have fewer adsorption pores but high adsorptivity. 773.15 K thermal treated coal has good CO2 adsorptivity and seepage capacity.